2005
DOI: 10.1002/ajh.20275
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of chronic graft‐versus‐host disease after allogeneic blood stem‐cell transplantation

Abstract: Allogeneic hematopoietic stem cells in peripheral blood transplantation (alloPBSCT) or bone marrow transplantation (alloBMT) have different biological characteristics which may affect differently prognostic factors for incidence and severity of chronic graft-versus-host disease (cGVHD). To determine the prognostic factors of cGVHD in patients receiving alloPBSCT, data on 87 patients who survived at least 100 days after matched related donor myeloablative transplantation were analyzed. Factors significantly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
2
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 31 publications
(43 reference statements)
3
35
2
1
Order By: Relevance
“…However, our analysis did not support previously reported risk factors for mortality in chronic GVHD, such as bilirubin levels, [12][13][14] Karnofsky performance status, 2,[15][16][17] female donor/male recipient pairing, 12,13 HLA mismatch, 13,16 older donor age, 13 and prior acute GVHD. 12,13,16 Additionally, insufficient data did not permit analysis of previously reported risk factors including response of chronic GVHD to therapy, 18,19 and steroid dose. 13 While overlap and late acute GVHD were associated with inferior outcome in univariable analysis, multivariable analysis did not support an independent association of chronic GVHD classification with overall survival or nonrelapse mortality.…”
Section: Discussioncontrasting
confidence: 54%
“…However, our analysis did not support previously reported risk factors for mortality in chronic GVHD, such as bilirubin levels, [12][13][14] Karnofsky performance status, 2,[15][16][17] female donor/male recipient pairing, 12,13 HLA mismatch, 13,16 older donor age, 13 and prior acute GVHD. 12,13,16 Additionally, insufficient data did not permit analysis of previously reported risk factors including response of chronic GVHD to therapy, 18,19 and steroid dose. 13 While overlap and late acute GVHD were associated with inferior outcome in univariable analysis, multivariable analysis did not support an independent association of chronic GVHD classification with overall survival or nonrelapse mortality.…”
Section: Discussioncontrasting
confidence: 54%
“…[10][11][12] The risk factors specific for the development of oral cGVHD are less well established; however, recent studies have described an association between oral GVHD and stem cell source, with an increased risk of oral GVHD in PBSCT (70%) relative to BMT (53%). 13 This association was also evident in our study, with a non-statistically significant trend suggesting that patients undergoing PBSCT had a higher prevalence of oral cGVHD (44%) relative to BMT (29%) and umbilical cord transplantation (25%). However, due to the very small study numbers of patients who underwent umbilical cord transplantation (n ¼ 4), this is unlikely to be a true representation of this group's risk for developing oral cGVHD.…”
Section: Oral Sites Involvedsupporting
confidence: 63%
“…14 The authors concluded that observed low platelet count may be a marker for a more severe form of cGVHD. 14 Pavletic et al 2 found platelets below 100 000/ml in cGVHD patients more frequently after alloBMT (41%) than after alloPSCT (27%), but the difference was not statistically significant. Similarly, Flowers et al 22 also did not find a statistically significant difference in prevalence of thrombocytopenia in cGVHD patients after alloBMT or alloPSCT.…”
Section: Transplant-related Thrombocytopeniamentioning
confidence: 99%
“…1 It is a systemic disorder characterized by immune deregulation, immunodeficiency, impaired organ function, development of signs and symptoms of various autoimmune or immunologic disorders, and is associated with decreased survival. [1][2][3][4] A low platelet count in cGVHD patients is among the most consistent and strongest negative survival predictors across cGVHD studies in both allogeneic bone marrow transplantation (alloBMT) and allogeneic peripheral stem cell transplantation (alloPSCT). 2,3,[5][6][7][8][9][10][11] Patients with cGVHD and persistent thrombocytopenia show poorer responses to therapy, experience higher mortality rates from infection or, less often, from hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation